AKTIVITAS ANTIDIABETES DARI TANAMAN FAMILI MYRTACEAE DENGAN INDUKSI ALOKSAN - Yustika Alfani; Siva Hamdani; Hesti Renggana (Fakultas Farmasi UMI, 2021)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia. This disease occurs due to abnormalities in insulin secretion, insulin work or both. Plants from the myrtaceae family that have been used traditionally as medicine and scientifically known to have various anti-inflammatory, anti-cancer, anti-diarrheal, antibacterial and antidiabetic activities. This review aims to provide information and efforts in the treatment of diabetes from several plants in the Myrtaceae family. The method used in this review is a literature review from various journals published online and I will discuss 8 plants from the myrtaceae family that are induced by alloxan. From the results it is known that of the 8 plants of the myrtaceae family that have been tested using alloxan induction has antidiabetic activity. Syzygium Polyanthum (Wight) is the most potential candidate in reducing blood glucose levels.